Test Dose Pharmacokinetics in Pediatric Patients Receiving Once‐Daily IV Busulfan Conditioning for Hematopoietic Stem Cell Transplant: A Reliable Approach?. (14th December 2017) - Brooks, Kristina M.; Jarosinski, Paul; Hughes, Thomas; Kang, Elizabeth; Shah, Nirali N.; Gall, John B. Le; Hickstein, Dennis D.; De Ravin, Suk See; George, Jomy M.; Kumar, Parag
Abstract: Intravenous (IV) busulfan test dose pharmacokinetics (PK) has been shown to accurately predict once‐daily dose requirements and improve outcomes in adult transplant patients, but there are limited data to support this approach in children. Test doses of busulfan ∼0.8 mg/kg were infused over 2 to 3 hours, followed by serial sampling to 4‐6 hours postinfusion in pediatric hematopoietic stem cell transplant recipients (n = 5). Once‐daily busulfan doses were calculated based on a myelosuppressive area under the concentration‐time curve (AUC) target of ∼3700 to 4000 μmol·min/L and assumed dose‐proportionality to the test dose. PK analysis was then repeated at full daily doses within 6‐8 days of test dose administration. Plasma PK samples collected under test and full‐dose conditions were analyzed using validated commercial assays and noncompartmental methods. In 4 out of 5 patients, PK estimates after once‐daily IV busulfan administration differed in comparison to test dose estimates (AUC range –38.2% to +49.7%, clearance range –34.3% to +61.8%). Patients 1, 2, and 3 required increases in remaining daily busulfan doses to achieve AUC targets, and no adjustment was required in patient 4. Patient 5's AUC was 49.7% higher than expected, and he subsequently developed fatal sinusoidal obstruction syndrome. In our experience with pediatric patients, test dose PK failed to reliably predict daily dosing requirements with large discrepancies from predicted AUC targets. This article highlights the necessity for therapeutic drug monitoring of IV busulfan and inadvisability of relying solely on test‐dose busulfan PK in pediatric patients. Furthermore, clinicians should consider strategies to expedite dose adjustments in real time.